2020
DOI: 10.1101/2020.04.17.20069237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forecasting of COVID-19 Cases and Deaths Using ARIMA Models

Abstract: After the outbreak of severe acute respiratory syndrome (SARS-2002/2003) and middle east respiratory syndrome (MERS-2012/2014) in the world, new public health crisis, called new coronavirus disease (COVID-19), started in China in December 2019 and has spread all over countries. COVID-19 coronavirus has been global threat of the disease and infected humans rapidly. Control of the pandemi is urgently essential, and science community have continued to research treatment agents. Support therapy and intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
(16 reference statements)
0
13
1
3
Order By: Relevance
“…Chintalapud et al (17) applied AIRMA model to forecast the confirmed infected and recovered COVID-19 cases in Italy after sixty days of lockdown. Bayyurt et al (18) has applied AIRIMA model to forecast COVID-19 cases and deaths in Italy, Spain and Turkey. Tandon et a (19) has developed an ARIMA model to forecast the COVID-19 cases in India.…”
Section: Introductionmentioning
confidence: 99%
“…Chintalapud et al (17) applied AIRMA model to forecast the confirmed infected and recovered COVID-19 cases in Italy after sixty days of lockdown. Bayyurt et al (18) has applied AIRIMA model to forecast COVID-19 cases and deaths in Italy, Spain and Turkey. Tandon et a (19) has developed an ARIMA model to forecast the COVID-19 cases in India.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of time series forecast of the COVID-19 epidemic have also been made, using ARIMA models [ 4 , 19 , 20 ], exponential smoothing [ 21 ], or autoregression in cases; for example, the study by Johndron et al [ 22 ] postulates daily deaths as a lagged function of earlier new cases. Applications of phenomenological models to COVID-19 incidence forecasts include the studies in [ 23 , 24 ].…”
Section: Related Research and Research Gapsmentioning
confidence: 99%
“…Lutfi and Burcu [ 17 ] performed Auto-Regressive Integrated Moving Average (ARIMA) model on the European Centre for Disease Prevention and Control (ECDC) COVID-19 data to predict the number of confirmed cases and deaths of COVID-19. The limitation of this particular study is that a limited number of countries were considered.…”
Section: Related Workmentioning
confidence: 99%